European first responder systems and differences in return of spontaneous circulation and survival after out-of-hospital cardiac arrest: A study of registry cohorts - Iris Oving, MSc; Corina de Graaf, MD, MSc; Siobhan Masterson, PhD; Rudolph W. Koster, MD, PhD; Aeilko H. Zwinderman, PhD, Professor; Remy Stieglis, MSc; Hajriz AliHodzic, MD, PhD; Enrico Baldi, MD; Susanne Betz, MD, PhD; Diana Cimpoesu, MD, PhD, Professor; Fredrik Folke, MD, PhD, Professor; Dennis Rupp; et al. (Elsevier, 2021)
Background: In Europe, survival-rates after out-of-hospital cardiac arrest (OHCA) vary widely between regions. Whether a system dispatching First Responders (FRs; main FR-types: firefighters, police officers, citizen-responders) is present or not may be associated with survival-rates. This study aimed to assess the association between having a dispatched FR-system and rates of return of spontaneous circulation (ROSC) and survival across Europe. Methods: Results of an inventory of dispatched FR-systems for OHCA in Europe were combined with aggregate ROSC and survival data from the EuReCa-TWO study and additionally collected data. Regression analysis (weighted on number of patients included per region) was performed to study the association between having a dispatched FR-system and ROSC and survival-rates to hospital discharge in the total population and in patients with shockable initial rhythm, witnessed OHCA and bystander cardiopulmonary resuscitation (CPR; Utstein comparator group). For regions without a dispatched FR-system, the theoretical survival-rate if a dispatched FR-system would have existed was estimated. Findings: We included 27 European regions. There were 15,859 OHCAs in the total group and 2,326 OHCAs in the Utstein comparator group. Aggregate ROSC and survival-rates were significantly higher in regions with an FR-system compared to regions without (ROSC: 36% [95%CI 35%-37%] vs. 24% [95%CI 23%-25%]; P<0.001; survival in total population [N=15.859]: 13% [95%CI 12%-15%] vs. 5% [95%CI 4%-6%]; P<0.001; survival in Utstein comparator group [N=2326]: 33% [95%CI 30%-36%] vs. 18% [95%CI 16%-20%]; P<0.001), and in regions with more than one FR-type compared to regions with only one FR-type. All main FR-types were associated with higher survival-rates (all P<0.050). Interpretation: European regions with dispatched FRs showed higher ROSC and survival-rates than regions without. Funding: This project/work has received funding from the European Union's Horizon 2020 research and innovation programme under acronym ESCAPE-NET, registered under grant agreement No 733381 (IO, HLT and MTB) and the European Union's COST programme under acronym PARQ, registered under grant agreement No CA19137 (IO, DC, HLT, MTB). HLT and MTB were supported by a grant from the Netherlands CardioVascular Research Initiative, Dutch Heart Foundation, Dutch Federation of University Medical Centres, Netherlands Organization for Health Research and Development, Royal Netherlands Academy of Sciences - CVON2017-15 RESCUED (HLT), and CVON2018-30 Predict2 (HLT and MTB).